Graphene sheet orientation of parent material exhibits dramatic influence on Graphene properties - Chua, Chun Kiang (2013)
The production of graphene from various sources has garnered much attention in recent years with the development of methods that range from “bottom-up” to “top-down” approaches. The top-down approach often requires thermal treatment to obtain a few-layered and lowly oxygenated graphene sheets. Herein, we demonstrate the production of graphene through oxidation and thermal-reduction/exfoliation of two sources of differently orientated graphene sheets: multiwalled carbon nanotubes (MWCNTs) and stacked graphene nanofibers (SGNFs). These two carbon-nanofiber-like materials have similar axial (length: 5–9 μm) and lateral dimensions (diameter: about 100 nm). We demonstrate that, whereas SGNFs exfoliate along the lateral plane between adjacent graphene sheets, carbon nanotubes exfoliate along its longitudinal axis and leads to opening of the carbon nanotubes owing to the built-in strain. Subsequent thermal exfoliation leads to graphene materials that have, despite the fact that their parent materials exhibited similar dimensions, dramatically different proportions and, consequently, materials properties. Graphene that was prepared from MWCNTs exhibited dimensions of about 5000×300 nm, whereas graphene that was prepared from SGNFs exhibited sheets with dimensions of about 50×50 nm. The density of defects and oxygen-containing groups on these materials are dramatically different, as are the electrochemical properties. We performed morphological, structural, and electrochemical characterization based on TEM, SEM, high-resolution X-ray photoelectron spectroscopy, Raman spectroscopy, and cyclic voltammetry (CV) analysis on the stepwise conversion of the target source into the exfoliated graphene. Morphological and structural characterization indicated the successful chemical and thermal treatment of the materials. Our findings have shown that the orientation of the graphene sheets in starting materials has a dramatic influence on their chemical, material, and electrochemical properties.